2017
DOI: 10.1371/journal.pone.0175470
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the gut bacterial microbiota of the bark beetle, Dendroctonus rhizophagus (Curculionidae: Scolytinae) across their life stages

Abstract: Bark beetles play an important role as agents of natural renovation and regeneration in coniferous forests. Several studies have documented the metabolic capacity of bacteria associated with the gut, body surface, and oral secretions of these insects; however, little is known about how the bacterial community structure changes during the life cycle of the beetles. This study represents the first comprehensive analysis of the bacterial community of the gut of the bark beetle D. rhizophagus during the insect’s l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 64 publications
3
51
0
1
Order By: Relevance
“…Firmicutes and Proteobacteria were the dominant phyla in Anoplophora glabripennis [ 12 ], Hylobius abietis [ 48 ], Monochamus alternatus and Psacothea hilaris [ 4 ], Nicrophorus vespilloides [ 26 ], and Popillia japonica [ 7 ]. Firmicutes, Proteobacteria and Bacteroidetes were also the dominant phyla in Holotrichia parallela [ 47 ], Dendroctonus valens [ 13 ], and Dendroctonus rhizophagus [ 10 ], and Tenericutes also was the dominant phylum in Odontolabis fallaciosa (Lucanidae) [ 34 ]. Prior research demonstrated that intestinal Firmicutes play significant role in the degradation of complex plant carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firmicutes and Proteobacteria were the dominant phyla in Anoplophora glabripennis [ 12 ], Hylobius abietis [ 48 ], Monochamus alternatus and Psacothea hilaris [ 4 ], Nicrophorus vespilloides [ 26 ], and Popillia japonica [ 7 ]. Firmicutes, Proteobacteria and Bacteroidetes were also the dominant phyla in Holotrichia parallela [ 47 ], Dendroctonus valens [ 13 ], and Dendroctonus rhizophagus [ 10 ], and Tenericutes also was the dominant phylum in Odontolabis fallaciosa (Lucanidae) [ 34 ]. Prior research demonstrated that intestinal Firmicutes play significant role in the degradation of complex plant carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the gut bacterial community of coleopteran pests to advance progress in pest control [ 10 , 11 ], including invasive bark beetles (Scolytidae) and longhorn beetles (Cerambycidae), that mainly feed on tree xylem and phloem. These species are considered to be serious pests of forests, as they grow and develop while feeding on lignocellulose [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study of the amphipod gut microbiota from the Mariana Trench, the draft genome of a Psychromonas strain (CDP1) was analyzed, which revealed a significant genome reduction driven by host association (22). Members of the genus Propionibacterium were found in the gut of the bark beetle Dendroctonus rhizophagus and are persistent in all life stages of this insect (23). Members of Pseudoalteromonas were detected in the gut microbiota of a variety of marine animals, such as the sea cucumber Apostichopus japonicus (24) and the small abalone Haliotis diversicolor (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using conventional techniques and massive parallel sequencing technologies have allowed the determination of the bacterial community structure associated with the inside (e.g., gut and mycangium) and the outside (e.g., mouthparts and cuticle) of the bark beetles body [ 7 , 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], galleries [ 29 ], and specific developmental stages of some species [ 30 , 31 ]. In addition, the presence of two core bacteriomes, one strict (composed by Enterobacter , Serratia , Rahnella , Pantoea , Raoultella , and Pseudomonas ) and another relaxed (constituted of the strict core plus Acinetobacter , Propionibacterium , Providencia , Stenotrophomonas , Erwinia , Kluyvera , Paenibacillus , and Ralstonia ) in the gut has been recently determined in different Dendroctonus species [ 28 ], which suggests that some of these taxa probably support basic metabolic processes that benefit these bark beetles.…”
Section: Introductionmentioning
confidence: 99%